Are Retirement Villages Promoting Active Aging? - Holt, Anne-Marie; Lee, Andy; Jancey, Jonine; Kerr, Deborah; Howat, Peter (2015)
PURPOSE: This study investigated physical activity (PA) facilities of retirement villages (RV) and neighborhood PA barriers identified by RV residents in Perth, Australia. METHODS: An environmental audit of PA facilities was undertaken on 50 RV with 50+ independent living units, using the Audit of Physical Activity Resources for Seniors. Telephone interviews with 200 RV residents were conducted to identify neighborhood barriers to walking, and to obtain information on utilization of facilities and attendance of PA programs. RESULTS: Larger size RV appeared to provide significantly more PA facilities and programs. Utilization of PA facilities and program attendance were low (˜ 50%) and not associated with the RV environment (size, age and facilities). Neighborhood barriers to walking were unsafe streets and hills. DISCUSSION: RV offers an attractive residential option with facilities that support active aging, but it is important to understand the barriers/enablers to utilize such facilities and attendance at programs offered.